Isolamento e caracterização fenotípica e molecular de parasitos Leishmania sp. de pacientes co leishmaniose tegumentar americana (LTA) atendidos no Hospital Universitário Lauro Wanderley da Universidade Federal da Paraíba. - Rodrigues, Yara Kátia Santos (2012)
Leishmaniasis is a complex of infectious and parasitic diseases endemic in 88 countries, that constitute a serious public health problem. Several species of the genus Leishmania are the causative agents of disease, among them the species L. (V.) braziliensis associated with different clinical manifestations of American Cutaneous Leishmaniasis (ACL). In the present study were obtained nine isolates of Leishmania sp. from cases of ACL. Seven isolates (87%) from patients residing in the municipalities of Pilões, and one (13%) resident in João Pessoa city, both Paraiba state regions. All nine strains were identified as L. (V.) braziliensis by specific PCR. Analyses of molecular characterization by RAPD-PCR showed that these isolates shared 62.63% revealing genotypic differences among them. However, the isolated AF and JSL, both from disseminated lesions had the highest percentage of shared bands among the isolates. Another molecular technique used was a SSR-PCR using the K7 primer, and it was also able to show polymorphism between isolates. In PCR-RLFP analysis of ITS1, different profiles were found among isolates, MRSS, JMTS, AF, JCTS, JRL showed the same band profile and the isolates JSL, JCNS, MFTS and JAS have each had, profiles different band. The analysis of hsp70 gene region by PCR-RLFP reveled that the isolates JSL, AF, JCTS, JRL, MFTS showed the same band profile and the isolates, MRSS, JMTS, JCNS and JAS had each one, different profiles band. In addition were also observed phenotypic differences between these isolates, since at an given time of cultivation, all showed different behavior, and demonstrate differences in sensitivity to drugs used in the treatment of leishmaniasis. Therefore, these studies show that the isolates of L. (V.) braziliensis obtained in the state of Paraiba demosntraram a significant genetic polymorphism, revealing a high level of intraspecific variation.